Construction of Forming Limit Diagram for Sheet Blanks from Aviation Aluminum Alloys - S. I. Feoktistov; I. K. Andrianov (Advanced Engineering Research, 2023)
Introduction. The modern development of stamping aircraft manufacturing is inextricably linked with the assessment of the limiting capabilities of sheet blanks. However, the issue of defect-free forming of blanks made of aviation aluminum alloys is understudied. The importance of this issue is due to the fact that aluminum alloys are often used in the manufacture of thin-walled products for aviation purposes. During the implementation of shaping processes, various defects may appear, specifically, corrugation or unacceptable thinning. In this regard, the objective of the work was to construct a diagram of the limit deformations of the base aviation alloys and to conduct a comparative analysis of the limit deformation curves for these materials.Materials and Methods. Logarithmic deformations with the property of additivity were used to account for large deformations. The construction of the diagram of the limit deformations was carried out in the formulation of the deformation theory of plasticity. The issue of constructing a diagram of limit deformations was considered on the basis of the positivity criterion of the loading force derivative. In the area of negative values of the smallest major deformations, the Hill criterion was used to construct the limit deformation curve, and in the area of positive values of the smallest major logarithmic deformations, the Swift criterion was used. When constructing the limit deformation diagram, a power approximation of the hardening rule was used.Results. The curves of limiting deformations for the following aviation alloys were obtained: AMg6, D16AT, AMg2M, 1201-T, AMcM. According to the comparative analysis of the areas of safe forming, the values of deformations of the beginning of necking and their influence on the change in the position of the curve of the limiting deformation of blanks were compared: the greater the deformation of the neck formation, the higher the position of the curve of the limiting deformations. The concept of the Keeler's limit deformation diagram was described. Approaches to the construction of the Hill-Swift criteria used on the basis of the results of tensile testing of sheet specimens were presented.Discussion and Conclusions. Based on the constructed curves of limiting deformations for aviation alloys, AMg-6, D16AT, AMg2M, 1201-T, AMcM, the following has been found. AMg2M alloy has the largest area of safe forming, 1201-T alloy has the smallest one. That is explained by the difference in relative deformations of the beginning of neck formation. The conducted research made it possible to evaluate the possibilities of defect-free forming of thin-walled blanks made of basic aviation aluminum alloys. The use of the constructed diagrams of limiting deformation will provide predicting the appearance of breaks in the process of forming sheet blanks.